2013
DOI: 10.4028/www.scientific.net/amm.319.485
|View full text |Cite
|
Sign up to set email alerts
|

The Applications of Neural Networks in the Engineering Cost of Transmission Line

Abstract: With the rapid development of the electric power industry in recent years, the strengthening of the power construction market and the diversification of the main body of power investment, there appears a prominent question in front of the project owners——How to control and reduce construction costs? There are many methods to estimate the cost quickly and accurately. Among the common methods and some new ways which have appeared in recent years, people can find about seven types out of them, in which, neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The principle of a Backpropagation (BP) neural network, also known as a multilayer perceptron (MLP), is to train a feedforward neural network using the backpropagation algorithm [25]. The BP neural network consists of multiple layers of interconnected neurons, including an input layer, one or more hidden layers, and an output layer [26].…”
Section: Proposed Approachmentioning
confidence: 99%
“…The principle of a Backpropagation (BP) neural network, also known as a multilayer perceptron (MLP), is to train a feedforward neural network using the backpropagation algorithm [25]. The BP neural network consists of multiple layers of interconnected neurons, including an input layer, one or more hidden layers, and an output layer [26].…”
Section: Proposed Approachmentioning
confidence: 99%
“…The experimental results showed that the method had a stable performance and could accurately estimate cost. Sun et al (2013) optimized the neural network using genetic algorithm and established a cost estimation model to realize the estimation of power engineering cost. Hsiao et al (2012) designed a new model to estimate the cost of semiconductor connection construction project by combining component ratio method, fuzzy adaptive learning control network (FALCON), fast chaotic genetic algorithm (fmGA) and three-point cost estimation method and verified through the study of 54 cases that the model had an estimation accuracy of 83.82 per cent.…”
Section: Introductionmentioning
confidence: 99%